Labour Regulation between neo-liberalism and statism An institutional approach and the example of the European Union - Pries, Ludger (Sociología del Trabajo, 2016)
Con respecto al impacto de la globalización en la regulación laboral predominan posturas “neoliberales-optimistas” y posturas “etatistas-pesimistas” que se reproducen mutuamente en constatar una desregulación, desnacionalización y mercantilización global. En este artículo se argumenta que hay regímenes institucionales de economía y sociedad que difieren sustancialmente a nivel nacional y regional. Por lo tanto, la relación entre globalización y regulación laboral es más complejo que el reflejado en los discursos mencionados. Esto se desarrolla tomando como ejemplo la Europeización y transnacionalización de la regulación laboral en los últimos diez años y el caso de Alemania en una visión comparativa europea. Labour Regulation between neo-liberalism and statism - an institutional approach and the example of the European Union Abstract Concerning the impact of globalization on labor regulation there are many dichotomous approaches either being optimistic of the process and promoting more liberalisation or being pessimistic of the process and advocating a critical or ‘progressive’ standpoint. Both extremes reinforce each other while one is applauding and the other criticising de-regulation, de-nationalisation and commodification. As an alternative to such dichotomous views the article proposes an approach of varying institutional regimes at national and regional level of economies and societies. Five social institutions are proposed to structure labor and economy, and also labor regulation. Labor regulation in the European Union and in Germany are taken as examples of the complex interplay between globalization and labor regulation.